The association between use of sunscreens and cosmetics and urinary concentrations of the UV filter ethylhexyl-methoxy cinnamate: a pilot biomonitoring study - Markogiannaki, Evangelia; Andrianou, Xanthi; Andra, Syam S.; Makris, Konstantinos C.; Kalyvas, Harris (My University, 2014)
Ethylhexyl-methoxy cinnamate (EHMC), an ultraviolet (UV) filter that absorbs solar UVB radiation is frequently used in the formulation of sunscreens and cosmetics. Except for the controlled UV filter application studies, no general population studies on the magnitude and variability of exposures to EHMC exist. Given the widespread use of UV filters in consumer products, a pilot human biomonitoring study was undertaken to: i) determine the concentrations of EHMC in urine samples of young adults, and ii) investigate the association between consumption patterns of selected consumer products and urinary EHMC concentrations. A group of 48 randomlyselected volunteers provided a first morning urine void and a questionnaire on the types and usage patterns of sunscreens and cosmetics was administered to them. Significantly (p=0.006) higher urinary EHMC levels were observed in females, and in users of face sunscreens (p=0.008) and lipsticks (p=0.003). Linear multiple regression analysis showed that the frequency of use of face sunscreens (all year) (p=0.02) and gender (females) (p=0.03) were significant predictors of creatinine-adjusted urinary EHMC levels in the pooled sample, even after adjusting for relevant covariates, such as age, body-mass index and the number of cosmetics used. A larger sample could help us further evaluate the observed trends.
Keywords: Octyl-methoxy cinnamate; Cosmetics; Biomonitoring; Sunscreens; UV filters; Exposure